Dehumidification / dew condensation prevention component carrying water vapor adsorbent and dehumidification / dew condensation prevention component manufacturing method
Patent Information
- Application Number
- JP2023139994
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-08-30
AI Technical Summary
【0015】 本発明によれば、基材として吸水性スポンジを用い、該スポンジの細孔内に、主成分であるアルミニウムケイ酸塩とともに水溶性バインダーを含有する水蒸気吸着材を担持させることにより、前記基材の厚みや形状に制限されずに前記アルミニウムケイ酸塩の充分な担持量を確保しつつ、幅広い湿度帯にて吸放湿が可能であり、特に、中~高湿度領域において高性能な吸着性能を有する除湿·結露防止部材を簡便な工程にて供給することができる。 また本発明によれば、水蒸気吸着材に、さらにヒアルロン酸及び/又はヒアルロン酸誘導体を含有させることにより、前記アルミニウムケイ酸塩が備える性能を著しく向上させるとともに、担持体である吸水性スポンジの細孔内により多くの量の水蒸気吸着材を担持させることが可能となる。
Smart Images

Figure 2025033936000001 
Figure 2025033936000002 
Figure 2025033936000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a member carrying a water vapor adsorbent and used for dehumidification and prevention of condensation (hereinafter referred to as a "dehumidification / condensation prevention member"), and to a method for producing the dehumidification / condensation prevention member. [Background technology]
[0002] High temperatures and humidity in the summer and condensation in the winter are major problems in daily life, and in order to create a comfortable living space, various methods of dehumidification and prevention of condensation using dehumidifying agents have been investigated. In this context, porous inorganic materials with nano-sized pores have the ability to adsorb water vapor based on their unique microstructure, and are therefore expected to be used as dehumidifiers, anti-condensation agents, autonomous humidity control materials, and the like.
[0003] Against the above background, the present inventors focused on the excellent affinity of aluminum silicate with water and, in order to improve its performance as a dehumidifier, proceeded with the development of a high-performance water vapor adsorbent capable of absorbing and releasing moisture over a wide range of humidity ranges, and discovered a substance consisting of amorphous aluminum silicate (see Patent Document 1) or a substance consisting of an aluminum silicate complex of low-crystalline layered clay and amorphous aluminum silicate (see Patent Document 2).
[0004] Furthermore, in order to further improve the adsorption performance of the above-mentioned aluminum silicate, it has been discovered that by adding hyaluronic acid and / or a hyaluronic acid derivative to the aluminum silicate, a water vapor adsorbent can be obtained that is capable of absorbing and releasing moisture over a wide range of humidity, and that has particularly improved adsorption performance in the medium to high humidity range (see Patent Document 3). However, the water vapor adsorbents described in the above Patent Documents 1 to 3 are in the form of powder itself, and as such cannot function as dehumidifying / condensation components or dehumidifying devices or condensation prevention devices, and it is therefore necessary to develop devices or components that can function as standalone devices.
[0005] It has already been proposed to make a dehumidifying device or a dehumidifying member using a substrate containing a water vapor adsorbent (dehumidifying agent) or a substrate coated or impregnated with a water vapor adsorbent (dehumidifying agent). For example, Patent Documents 4 and 5 propose using a porous metal oxide such as silica gel, or a mixture of an aluminum silicate, a porous metal oxide such as silica gel, and a hygroscopic salt as a dehumidifying agent, mixing the dehumidifying agent with a fibrous material and making paper, or coating the dehumidifying agent on a sheet-like substrate to produce a dehumidifying sheet or dehumidifying filter. The dehumidifying sheets and dehumidifying filters described in these patent documents can be regenerated at low temperatures of 40° C. to less than 80° C., and therefore can be suitably used as dehumidifying rotors in desiccant air conditioners.
[0006] Patent Document 6 proposes a method of controlling humidity under the floor using a granular humidity conditioner containing a specific hydrated iron-containing aluminum oxide, which describes laying a moisture-proof sheet under the floor and providing a layer of the granular humidity conditioner on the moisture-proof sheet (see claim 7), or laying a sheet containing the granular humidity conditioner and having at least an upper surface that is breathable under the floor (see claim 8). The patent document also describes dispersing hydrated iron-containing aluminum oxide in water with natural or synthetic fibers and mixing them to obtain paper, dispersing hydrated iron-containing aluminum oxide in water and impregnating a sheet substrate with it to obtain a sheet-type deodorant, or forming a nonwoven fabric using fibers as the raw material (paragraph
[0036] ).
[0007] Furthermore, Patent Document 7 proposes a dehumidifier consisting of multiple metal cylinders filled with a dehumidifying agent and a frame body with legs that holds the multiple cylinders, and describes that the dehumidifying agent is calcium chloride or lithium chloride impregnated into a nonwoven fabric, sponge, or pipe (see claim 6).Then, in the examples (column 3, lines 16-18), it describes that a pulp material that has been impregnated with an aqueous calcium chloride solution and then dried is filled inside a metal cylinder with many holes. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2017-128499 A [Patent Document 2] JP 2019-026487 A [Patent Document 3] Patent application No. 2022-211946 [Patent Document 4] JP 2012-200644 A [Patent Document 5] JP 2011-194352 A [Patent Document 6] JP 2003-033624 A [Patent Document 7] JP 2002-326011 A Summary of the Invention [Problem to be solved by the invention]
[0009] As described above, aluminum silicate can provide a water vapor adsorbent that can absorb and release moisture over a wide range of humidity levels, so there is a demand for the development of dehumidifying and condensation prevention materials that contain aluminum silicate as their main component.
[0010] The dehumidifying sheets and dehumidifying filters described in Patent Documents 4 and 5 can be suitably used as dehumidifying rotors in desiccant air conditioners. However, because the regeneration of the dehumidifying agent (the desorption of adsorbed water vapor) requires the blowing of air heated to a low temperature, there is a problem that they are not suitable as dehumidifying and condensation prevention members that are installed in desired locations, such as under the floor or ceiling of a house, to prevent high temperatures and humidity in summer and condensation in winter. Furthermore, when a dehumidifying sheet is made by mixing a dehumidifying agent with a fibrous material and making the mixture into paper, not only is the papermaking process necessary, but there are also limitations to the thickness and shape of the sheet that can be obtained, making it difficult to increase the amount of dehumidifying agent that can be carried.
[0011] In order to obtain the granular humidity control agent made of a specific hydrated iron-containing aluminum oxide granule as described in the above-mentioned Patent Document 6, a separate step of forming the granules by extrusion molding or the like is required, and it cannot be said to be a simple method. In addition, the Patent Document also describes mixing the hydrated iron-containing aluminum oxide with fibers and making paper or nonwoven fabric, but as in the above, there is a problem that the thickness and shape of the obtained sheet are limited, and it is difficult to increase the amount of the humidity control agent carried. Furthermore, the Patent Document does not specifically disclose the sheet substrate other than the above-mentioned fiber used for making paper or nonwoven fabric. Furthermore, Patent Document 7 only describes impregnating a substrate with an aqueous solution of calcium chloride or lithium chloride, and does not disclose aluminum silicate.
[0012] The present invention has been made in consideration of the above circumstances, and has an object to provide a dehumidifying and condensation prevention member that is capable of absorbing and releasing moisture over a wide range of humidity levels, and has particularly high adsorption performance in the medium to high humidity range, by using a substrate that can easily support a sufficient amount of aluminum silicate, without being limited by thickness or shape, as a substrate that supports the main component aluminum silicate, and to provide a method for manufacturing the dehumidifying and condensation prevention member. [Means for solving the problem]
[0013] As a result of extensive investigations aimed at achieving the above-mentioned object, the inventors discovered that by impregnating an absorbent sponge with an aqueous slurry comprising a mixture of aluminum silicate powder, a water-soluble binder, and water, or further containing hyaluronic acid and / or a hyaluronic acid derivative, it is possible to obtain a dehumidifying and condensation prevention member capable of absorbing and releasing moisture over a wide range of humidity, and which has improved adsorption performance particularly in the medium to high humidity range, thereby completing the present invention.
[0014] That is, the present invention for solving the above problems includes the following aspects. [1] A dehumidifying and condensation prevention material in which a water vapor adsorbent containing aluminum silicate and a water-soluble binder is supported within the pores of a water-absorbent sponge. [2] The dehumidifying and condensation prevention member according to [1], wherein the water vapor adsorbent contains hyaluronic acid and / or a hyaluronic acid derivative. [3] The dehumidifying and condensation prevention member according to [1] or [2], wherein the sponge has an average pore size of 90 to 1000 μm. [4] The density of the water vapor adsorbent in the sponge is 0.04 g / cm 3 The above-mentioned dehumidification / condensation prevention member according to any one of [1] to [3]. [5] The dehumidifying and condensation prevention member according to any one of [1] to [4], wherein the aluminum silicate is an amorphous aluminum silicate or an aluminum silicate complex comprising a low-crystalline layered clay mineral and an amorphous aluminum silicate. [6] The moisture-wicking and condensation prevention member according to any one of [1] to [5], wherein the water-soluble binder is polyvinyl alcohol. [7] A step of impregnating an absorbent sponge with an aqueous slurry containing an aluminum silicate and a water-soluble binder; and drying the sponge impregnated with the aqueous slurry; The method for producing a dehumidifying and condensation prevention member includes the steps of: [8] The method for producing a dehumidifying and condensation prevention member according to [7], wherein the aqueous slurry contains hyaluronic acid and / or a hyaluronic acid derivative. [9] The method for producing a dehumidifying and condensation prevention member according to [7] or [8], wherein the aqueous slurry is vibrated in the step of impregnating the sponge with the aqueous slurry.
[10] The method for producing a dehumidifying and condensation prevention member according to any one of [7] to [9], wherein the sponge has an average pore size of 90 to 1000 μm.
[11] The method for producing a dehumidifying and condensation prevention member according to any one of [7] to
[10] , wherein the aluminum silicate is an amorphous aluminum silicate or an aluminum silicate complex comprising a low-crystalline layered clay mineral and an amorphous aluminum silicate.
[12] The method for producing a dehumidifying and condensation prevention member according to any one of [7] to
[11] , wherein the water-soluble binder is polyvinyl alcohol. Effect of the Invention
[0015] According to the present invention, by using an absorbent sponge as a substrate and supporting a water vapor adsorbent material containing aluminum silicate as the main component and a water-soluble binder in the pores of the sponge, it is possible to ensure a sufficient amount of aluminum silicate supported without being limited by the thickness or shape of the substrate, while enabling moisture absorption and desorption over a wide humidity range.In particular, a dehumidifying and condensation prevention member with high-performance adsorption performance in the medium to high humidity range can be supplied in a simple process. Furthermore, according to the present invention, by further incorporating hyaluronic acid and / or a hyaluronic acid derivative into the water vapor adsorbent, the performance of the aluminum silicate is significantly improved and a greater amount of the water vapor adsorbent can be supported within the pores of the absorbent sponge, which serves as the support. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The following describes a dehumidifying / condensation prevention member and its manufacturing method in an embodiment of the present invention (hereinafter referred to as the present embodiment), but the present invention is not limited to the present embodiment. Furthermore, among the components in the present embodiment, those components that are not described in the claims showing the highest concept are described as optional components. In addition, when a numerical range is expressed using "~", it means that the numerical values stated as the lower limit and upper limit are also included.
[0017] <Dehumidification and condensation prevention materials> The moisture-removing and condensation prevention member of this embodiment is characterized in that a water vapor adsorbent containing aluminum silicate and a water-soluble binder is supported within the pores of a water-absorbent sponge.
[0018] <Water vapor adsorbent> The water vapor adsorbent of this embodiment contains an aluminum silicate and a water-soluble binder, and preferably further contains hyaluronic acid and / or a hyaluronic acid derivative.
[0019] (Aluminum Silicate) The aluminum silicate used in the water vapor adsorbent of this embodiment is the main component of the water vapor adsorbent, and is a hydrated aluminum silicate whose constituent elements are silicon (Si), aluminum (Al), oxygen (O) and hydrogen (H) and is assembled by numerous Si-O-Al bonds. Specifically, the aluminum silicate used in this embodiment is an amorphous aluminum silicate, or an aluminum silicate complex consisting of a low-crystalline layered clay mineral and an amorphous aluminum silicate (hereinafter, sometimes simply referred to as an "aluminum silicate complex").
[0020] The aluminum silicate used in the water vapor adsorbent of this embodiment can be artificially obtained by mixing and stirring an aqueous solution or aqueous dispersion of an inorganic silicon compound as the raw material for the silicon source and an inorganic aluminum compound as the raw material for the aluminum source, and then desalting (washing) and heating the resulting precursor (see Patent Documents 1 and 2, etc.), but it can also be purchased commercially.
[0021] (Water-soluble binder) The water vapor adsorbent of this embodiment contains a water-soluble binder in addition to the aluminum silicate that is the main component. By incorporating a water-soluble binder into the water vapor adsorbent of the present invention, it is possible to support a sufficient amount of water vapor adsorbent within the pores of the sponge support without affecting the moisture absorption and release performance of the aluminum silicate.
[0022] The water-soluble binder used in the water vapor adsorbent of the present invention is not particularly limited as long as it is water-soluble and can form an aqueous slurry when mixed with water together with the aluminum silicate powder. Examples of water-soluble binders include polyvinyl alcohol (PVA), sugars, phenol resins, polycarboxylic acid resins, etc. Among these, polyvinyl alcohol (PVA) is preferred because it is inexpensive, highly safe, and easily available. Polyvinyl alcohol (PVA) may have vinyl acetate units in addition to vinyl alcohol units.
[0023] (Aluminum silicate and water-soluble binder content) The content of aluminum silicate and water-soluble binder in the water vapor adsorbent of this embodiment, in terms of mass percent on a dry basis, is 80 to 99 mass percent aluminum silicate and 1 to 20 mass percent water-soluble binder, and more preferably 85 to 95 mass percent aluminum silicate and 5 to 15 mass percent water-soluble binder.
[0024] (Hyaluronic acid and / or hyaluronic acid derivatives) The water vapor adsorbent of this embodiment preferably further contains hyaluronic acid and / or a hyaluronic acid derivative. The hyaluronic acid and / or hyaluronic acid derivative used in the water vapor adsorbent of this embodiment is a hydrophilic polymer having hygroscopic properties. In the water vapor adsorbent of this embodiment, by containing hyaluronic acid and / or a hyaluronic acid derivative together with aluminum silicate, the performance of the aluminum silicate is significantly improved; specifically, the moisture absorption and desorption performance over a wide range of humidity is further improved, resulting in a water vapor adsorbent that exhibits high-performance adsorption performance particularly in the medium to high humidity range. Furthermore, in the water vapor adsorbent of this embodiment, by containing hyaluronic acid and / or a hyaluronic acid derivative in addition to the water-soluble binder, it is possible to support a sufficient amount of the water vapor adsorbent within the pores of the sponge, which serves as the support.
[0025] In this embodiment, the hyaluronic acid used is not particularly limited, but may be, for example, a disaccharide polymer consisting of glucuronic acid and N-acetylglucosamine, with an average molecular weight of 50,000 to 10,000,000 Daltons. Hyaluronic acid can be produced by a known method, or hyaluronic acid itself can be obtained from the market.
[0026] In this embodiment, free hyaluronic acid can be used, or its salt can be used.The salt of hyaluronic acid used in the present invention is not particularly limited, but can be, for example, sodium salt, potassium salt, calcium salt, aluminum salt, zinc salt, iron salt, ammonium salt, tetrabutylammonium salt, etc.As mentioned above, such hyaluronic acid salt can be easily obtained from the market.In addition, hyaluronic acid obtained from the market can be made into salt by well-known method to prepare hyaluronic acid salt.
[0027] Examples of hyaluronic acid derivatives include hyaluronic acid having hydrophilic groups such as sulfonic acid groups, phosphoric acid groups, and amino groups in the side chain or main chain, hyaluronic acid further having increased hydroxyl groups or carboxyl groups, and hyaluronic acid having carboxyl groups converted into hyaluronate salts by sodium ions, potassium ions, etc. Among them, hyaluronic acid and / or hyaluronic acid derivatives used in the water vapor adsorbent of this embodiment are preferably hyaluronate salts, and such hyaluronate salts are easily available on the market.
[0028] The hyaluronic acid derivative that can be used in this embodiment can be the one that introduces hydrophilic group into the molecule, as well as the one that has the hyaluronic acid skeleton derived from hyaluronic acid.Such hyaluronic acid derivative is not particularly limited, but can be, for example, the one or more carboxyl groups in hyaluronic acid are esterified, the one or more hydroxyl groups in hyaluronic acid are partially crosslinked with formaldehyde and further polymerized, and the acetylated hyaluronic acid, etc.
[0029] In this embodiment, at least one type of hyaluronic acid or at least one type of hyaluronic acid derivative may be used, or at least one type of hyaluronic acid and at least one type of hyaluronic acid derivative may be used in combination.
[0030] (Hyaluronic acid and / or hyaluronic acid derivative content) When the water vapor adsorbent of this embodiment contains hyaluronic acid and / or a hyaluronic acid derivative, the content of the hyaluronic acid and / or the hyaluronic acid derivative in the entire water vapor adsorbent is, in terms of mass percent when dried, 0.01 to 10 mass percent, and more preferably 0.01 to 0.1 mass percent.
[0031] (Other Ingredients) The water vapor adsorbent of this embodiment may contain any other components in addition to the above-mentioned essential components and the optional components of hyaluronic acid and / or hyaluronic acid derivatives, as long as the effects of the present invention are not impaired.
[0032] <Water-absorbent sponge> In the dehumidifying and condensation prevention member of this embodiment, the water-absorbent sponge is used as a support that carries within its pores a water vapor adsorbent material containing the above-mentioned aluminum silicate and a water-soluble binder, or further containing hyaluronic acid and / or a hyaluronic acid derivative. Therefore, the water-absorbent sponge in this embodiment is not particularly limited as long as it can support at least aluminum silicate and a water-soluble binder in its pores. Specifically, any sponge having open cells may be used, including natural sponges and synthetic sponges, such as sea sponges, urethane sponges, and urethane foams. In this embodiment, the water-absorbent sponge preferably has an average pore size of 90 to 1000 μm.
[0033] In the dehumidifying and condensation prevention member of this embodiment, the shape of the water-absorbent sponge is not particularly limited, and it can be in a sheet shape or any other shape depending on the application of the dehumidifying and condensation prevention material described later. In addition, in the dehumidifying and condensation prevention member of this embodiment, the thickness of the water-absorbent sponge is not particularly limited, but as shown in the examples described later, the loading density of the water vapor adsorbent decreases as the thickness increases. On the other hand, the loading amount decreases when the thickness is reduced, so in that case, this can be solved by stacking the water-absorbent sponge, which is the base material.
[0034] (Water vapor adsorbent loading density in water-absorbent sponge) In the dehumidifying and condensation prevention member of this embodiment, the loading density of the water vapor adsorbent supported in the pores of the water absorbent sponge can be changed by the average pore size and thickness of the water absorbent sponge used, the presence or absence of hyaluronic acid and / or hyaluronic acid derivatives in the water vapor adsorbent, or whether vibration is applied in the impregnation step described later, as shown in the examples described later. By combining these conditions, 3 It can be more than that.
[0035] <Manufacturing method for dehumidifying and condensation prevention materials> The method for producing the dehumidification and condensation prevention member in this embodiment is as follows: (I) impregnating an absorbent sponge with an aqueous slurry containing an aluminum silicate and a water-soluble binder; and (II) drying the sponge impregnated with the aqueous slurry; Includes.
[0036] (Preparation of aqueous slurry) An aqueous solution of a water-soluble binder and water are added to aluminum silicate powder, or an aqueous solution of a water-soluble binder, hyaluronic acid and / or a hyaluronic acid derivative, and water are added to aluminum silicate powder, and the mixture is mixed well to prepare an aqueous slurry. It is essential that the particle size of the aluminum silicate powder is sufficiently smaller than the pore size of the sponge on which it is supported, and it is preferably 0.5 to 100 μm, and more preferably 1 to 10 μm. Prior to preparation of the aqueous slurry for impregnation, the aluminum silicate powder may be subjected to pulverization or classification, if necessary, in order to adjust the particle size thereof.
[0037] (Impregnation process / Drying process) The method for impregnating the water-absorbent sponge with the aqueous slurry is not particularly limited, but it is preferable to immerse the water-absorbent sponge in the aqueous slurry prepared above to impregnate the sponge with the aqueous slurry. When the sponge is immersed in the aqueous slurry, the aqueous slurry can be vibrated to allow the aqueous slurry to penetrate into the pores of the water-absorbent sponge. The method for imparting vibration to the aqueous slurry is not particularly limited, but examples include a method in which a space potential generating device such as DENBA+2.0 manufactured by DENBA Corporation is used to impart low-frequency vibration of 20 to 100 Hz to the aqueous slurry. Next, the sponge impregnated with the aqueous slurry is dried. The drying temperature and time are not particularly limited as long as the sponge is not melted by heat, but is preferably 20 to 70°C, and more preferably 30 to 60°C. After drying, the solid matter adhering to the outer surface of the sponge without being supported within the pores of the sponge may be removed to prevent the solid matter from being detached from the sponge.
[0038] <Applications for dehumidifying and condensation prevention materials> The dehumidifying / condensation prevention member of this embodiment is capable of absorbing and releasing moisture over a wide range of humidity, and has particularly high adsorption performance in the medium to high humidity range. Therefore, its applications are not particularly limited, and it can be used in various applications where a dehumidifying / condensation prevention member is required. Specifically, for example, they can be installed in desired locations such as under the floor or in the ceiling of a house to prevent high temperatures and humidity in the summer and condensation in the winter. They can also be used as dehumidifying sheets for closets and chests of drawers, and as interior materials such as wallpaper and flooring. EXAMPLES
[0039] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these in any way.
[0040] <Production of Aluminum Silicate Complex> In the examples, powder of aluminum silicate complex was used. The powder of aluminum silicate complex was produced by using 1000mL of water glass aqueous solution with Si concentration of 495mmol / L as silicon source (Si source) and 1000mL of aluminum sulfate aqueous solution with Al concentration of 450mmol / L as aluminum source (Al source).
[0041] The water glass aqueous solution was added to the aluminum sulfate aqueous solution, and the mixture was stirred for about 15 minutes. The Si / Al molar ratio at this time was 1.1. After stirring, a 5N sodium hydroxide aqueous solution was added until the pH reached about 7, and a suspension was obtained. The amount of the sodium hydroxide aqueous solution dropped was 12 mL. The obtained suspension was stirred for 1 hour to prepare a precursor suspension. The prepared 1000 mL precursor suspension was washed three times by centrifugation, and 1000 mL of the precursor suspension was prepared again. 70 mL of the obtained precursor suspension was placed in a Teflon (registered trademark) container and heated at 200°C for 6 hours. The mixture was then dried at 60°C for 1 day and then pulverized to obtain a powder having a particle size of 1 to 10 μm.
[0042] The powder was subjected to powder X-ray diffraction measurement. The powder X-ray diffraction pattern showed broad peaks at 2θ = 20°, 26°, 35°, and 40°, confirming the formation of an aluminum silicate complex.
[0043] <Preparation of aqueous slurry> To 60 g of the aluminum silicate complex powder obtained above, 50 g of a 10% aqueous solution of polyvinyl alcohol (Kaneyonol, manufactured by Kaneyo Soap Co., Ltd.) and 140 g of water were added and mixed well to prepare an aqueous slurry (1). In addition, 0.3 g of sodium hyaluronate (sodium hyaluronate powder, manufactured by Horus Co., Ltd.), 50 g of a 10% aqueous polyvinyl alcohol solution, and 140 g of water were added to 60 g of the aluminum silicate complex powder obtained above, and the mixture was thoroughly mixed to prepare an aqueous slurry (2). Further, 140 g of water was added to 60 g of the aluminum silicate complex powder obtained above and mixed thoroughly to prepare an aqueous slurry (3).
[0044] <Production of dehumidifying and condensation prevention materials> Example 1 A urethane sponge (manufactured by Yawata Neji Co., Ltd., uneven cushion 30 small wave) with a length of 3 cm, width of 3 cm, thickness of 2.5 cm and average pore diameter of 1000 μm was immersed in the aqueous slurry (1) not containing hyaluronic acid obtained above for 15 minutes, and then dried at 40°C, and the solid matter on the surface was removed to obtain a dehumidifying and condensation prevention member. Example 2 A dehumidifying / condensation prevention member was obtained in the same manner as in Example 1, except that the aqueous slurry (2) containing hyaluronic acid obtained above was used as the aqueous slurry. (Comparative Example) A dehumidifying / condensation prevention member was obtained in the same manner as in Example 1, except that the aqueous slurry (3) obtained above was used as the aqueous slurry.
[0045] <Adsorbent loading density in dehumidifying and condensation prevention materials> In the dehumidification and condensation prevention members obtained in Examples 1 and 2 (and Comparative Example), the amount (g) and density (g / cm) of the water vapor adsorbent supported on each member were 3 ) are shown in Table 1. The supported amount (g) was determined by weighing a sponge that was not impregnated with the aqueous slurry after drying it at 40°C for 24 hours, and subtracting the mass (g) of the sponge that was not impregnated with the aqueous slurry from the weighed mass (g) of the dehumidification / condensation prevention members obtained in Examples 1 and 2 and the Comparative Example.
[0046] [Table 1]
[0047] The results shown in Table 1 reveal that in the comparative examples in which PVA was not used, the amount carried was reduced to about 64% compared to the cases in which PVA was used (both without hyaluronic acid). It is also apparent that the loading amount (g) can be increased by using hyaluronic acid (mass ratio to aluminum silicate: 0.5%) in combination.
[0048] <Water vapor adsorption evaluation> The dehumidification and condensation prevention members obtained in Examples 1 and 2 were evaluated for water vapor adsorption. (Evaluation method) The dehumidification and condensation prevention members obtained in Examples 1 and 2, and the sponge not impregnated with the aqueous slurry were used for evaluation. Each member was dried at 40°C for 24 hours to remove solids from the surface, and then weighed. The dry mass of each member was determined by subtracting the mass of the sponge not impregnated with the aqueous slurry from the dry mass. The members were then placed in a thermohygrostat at 25°C and a relative humidity of 95% to adsorb water vapor, and the masses were measured after 0.5 hours, 1 hour, 1.5 hours, 3 hours, 6 hours, and 24 hours, and the mass after subtracting the mass of the sponge not impregnated with the aqueous slurry was determined as the mass after adsorption. The adsorption rate was calculated from the dry mass and the mass after adsorption using the following formula. Adsorption rate (%) = (mass after adsorption - dry mass) ÷ dry mass × 100 After further adsorption for 24 hours, the sample was placed in a thermo-hygrostat at 25°C and a relative humidity of 60%, and the mass was measured after 12 hours of regeneration (total of 36 hours). The adsorption rate (%) after 12 hours of regeneration was calculated in the same manner as above. The results of the water vapor adsorption evaluation are shown in Table 2.
[0049] [Table 2]
[0050] The results shown in Table 2 demonstrate that the performance of aluminum silicate can be improved by including hyaluronic acid.
[0051] From the above results, it is preferable that the aqueous impregnation slurry contains hyaluronic acid. In the following examples, the effects of pore size and vibration were investigated using the aqueous impregnation slurry (2).
[0052] <Consideration of pore size> <Production of dehumidifying and condensation prevention materials> Example 3 A urethane sponge (manufactured by AION Co., Ltd., product number PU-N1T) having a length of 5 cm, a width of 5 cm, a thickness of 0.1 cm, and an average pore diameter of 25 μm was immersed in the aqueous slurry (2) obtained above for 15 minutes, and after drying at 40° C., the solid content on the surface was removed to obtain a dehumidifying and condensation prevention member.
[0053] Example 4 A urethane sponge (manufactured by AION Co., Ltd., product number PU-N5T) having a length of 5 cm, a width of 5 cm, a thickness of 0.5 cm, and an average pore diameter of 25 μm was immersed in the aqueous slurry (2) obtained above for 15 minutes, and after drying at 40° C., the solid content on the surface was removed to obtain a dehumidifying and condensation prevention member.
[0054] Example 5 A urethane sponge (manufactured by Fuji Chemical Co., Ltd., product number 1 mm size 1200 × 600 mm) having a length of 5 cm, a width of 5 cm, a thickness of 0.5 cm, and an average pore diameter of 90 μm was immersed in the aqueous slurry (2) obtained above for 15 minutes, and after drying at 40 ° C., the solid content on the surface was removed to obtain a dehumidifying and dew condensation prevention member.
[0055] Example 6 A urethane sponge (manufactured by Fuji Chemical Co., Ltd., product number 5 mm, size 1200 × 600 mm) having a length of 5 cm, a width of 5 cm, a thickness of 0.1 cm, and an average pore diameter of 150 μm was immersed in the aqueous slurry (2) obtained above for 15 minutes, and after drying at 40 ° C., the solid content on the surface was removed to obtain a dehumidifying and dew condensation prevention member.
[0056] <Adsorbent loading density in dehumidifying and condensation prevention materials> In the same manner as in Example 2, the loading density of the water vapor adsorbent loaded on the dehumidifying and condensation preventing members obtained in Examples 3 to 6 was determined. The results are shown in Table 3 together with the results obtained in Example 2.
[0057] [Table 3]
[0058] As shown in Table 3, the results of Examples 3 and 6 and Examples 4 and 5, which have the same thickness, reveal that the loading density of the water vapor adsorbent in dehumidifying and condensation prevention components increases as the pore diameter increases.
[0059] 《Effect of vibration on the production of dehumidifying and condensation prevention materials》 (Examples 7 to 11) The dehumidification / condensation prevention members of Examples 7 to 11 were obtained in the same manner as in Examples 3 to 6 and Example 2, respectively, except that the water-absorbent sponge was immersed in the aqueous slurry (2) obtained above while vibrating the slurry using a vibrating device (DENBA+2.0, manufactured by DENBA Corporation).
[0060] <Adsorbent loading density in dehumidifying and condensation prevention materials> Table 4 shows the loading density of the water vapor adsorbent loaded on the dehumidifying and condensation prevention members obtained in Examples 3 to 6, 2 and Examples 7 to 11, divided into conditions with and without vibration during immersion.
[0061] [Table 4]
[0062] As shown in Table 4, it was clear that when the average pore diameter was 150 to 1000 μm, the loading density was higher with vibration.
[0063] <Water vapor adsorption evaluation> The moisture adsorption amount of the dehumidifying and condensation prevention members obtained in Examples 2 to 11 was evaluated. (Evaluation Method) Evaluation was carried out using the dehumidifying and condensation prevention members obtained in Examples 2 to 11 and the sponge not impregnated with the aqueous slurry. Each member was dried at 40°C for 24 hours, and then weighed. The mass of the sponge not impregnated with the aqueous slurry for impregnation was subtracted from the dry mass of each member. Next, the member was placed in a thermohygrostat at 25°C and a relative humidity of 95% to adsorb water vapor, and the mass was measured after 0.5 hours, 1 hour, 1.5 hours, 3 hours, 6 hours, and 24 hours, and the mass of the sponge not impregnated with the aqueous slurry was subtracted from the dry mass to obtain the mass after adsorption. The adsorption rate was calculated from the dry mass and the mass after adsorption using the following formula. Adsorption rate (%) = (mass after adsorption - dry mass) ÷ dry mass × 100 After further adsorption for 24 hours, the sample was placed in a thermo-hygrostat at 25°C and a relative humidity of 60%, and the mass was measured after 12 hours of regeneration (total of 36 hours). The adsorption rate (%) after 12 hours of regeneration was calculated in the same manner as above. The results of the evaluation of the water vapor adsorption amount are shown in Table 5.
[0064] [Table 5]
[0065] The results in Table 5 show that the 0.1 cm thick components (Examples 3, 7, 6, 10) had a large adsorption amount from 0.5 to 1 hour, with water vapor adsorption completing in approximately 1 hour, whereas the components with a thickness of 0.5 cm or more (Examples 4, 8, 5, 9: 0.5 cm; Examples 2, 11: 2.5 cm) showed an increase in the amount of water vapor adsorption with adsorption time, with adsorption completing in approximately 3 hours. It was revealed that the adsorption amount per unit volume exceeded 10 wt % in 0.5 hours in members having pore sizes of 90 μm or more (Examples 5, 9, 6, 10, 2, and 11). Furthermore, when the relative humidity was lowered to 60% after 24 hours of adsorption, the adsorbed moisture was desorbed in all materials, demonstrating that the lower relative humidity enabled drying.
Claims
1. A moisture-removing and condensation-preventing member in which a water vapor adsorbent containing aluminum silicate and a water-soluble binder is supported within the pores of a water-absorbent sponge.
2. 2. The dehumidifying and condensation preventing member according to claim 1, wherein the water vapor adsorbent contains hyaluronic acid and / or a hyaluronic acid derivative.
3. 3. The dehumidification and condensation prevention member according to claim 1, wherein the sponge has an average pore size of 90 to 1000 μm.
4. The density of the water vapor adsorbent in the sponge is 0.04 g / cm 3 The dehumidification and condensation prevention member according to claim 1 or 2.
5. 3. The dehumidification and condensation prevention member according to claim 1, wherein the aluminum silicate is an amorphous aluminum silicate or an aluminum silicate complex comprising a low-crystalline layered clay mineral and an amorphous aluminum silicate.
6. 3. The moisture-wicking and condensation-preventing member according to claim 1, wherein the water-soluble binder is polyvinyl alcohol.
7. A step of impregnating an absorbent sponge with an aqueous slurry containing an aluminum silicate and a water-soluble binder; and drying the sponge impregnated with the aqueous slurry; A method for producing a dehumidifying and condensation prevention member comprising the steps of:
8. The method for producing a dehumidifying and condensation prevention member according to claim 7 , wherein the aqueous slurry contains hyaluronic acid and / or a hyaluronic acid derivative.
9. 9. The method for producing a dehumidification and condensation prevention member according to claim 7 or 8, wherein the water-based slurry is vibrated in the step of impregnating the sponge with the water-based slurry.
10. The method for manufacturing a dehumidification and condensation prevention member according to claim 7 or 8, wherein the sponge has an average pore size of 90 to 1000 μm.
11. 9. The method for producing a dehumidification and condensation prevention member according to claim 7 or 8, wherein the aluminum silicate is an amorphous aluminum silicate or an aluminum silicate complex comprising a low-crystalline layered clay mineral and an amorphous aluminum silicate.
12. The method for producing a moisture-dehumidifying and condensation-preventing member according to claim 7 or 8, wherein the water-soluble binder is polyvinyl alcohol.
Citation Information
Patent Citations
Hyaluronic acid silk fabric and making method thereof
CN109537279A
Post-finishing process of hyaluronic acid real silk fabric
CN111021061A
Purification method of sodium hyaluronate
CN112940148A
Ozone absorber
JP1979141375A
- Hygroscopic sealing plate
JP1983078135U